Changes in 24-Hour Domain-Specific Movement Behaviors and Their Associations With Children's Psychosocial Health During the Transition From Primary to Secondary School: A Compositional Data Analysis - Chong, Kar Hau; Dumuid, Dorothea; Cliff, Dylan P; Parrish, Anne-Maree; Okely, Anthony D (My University, 2022)
Little is known about the influence of 24-hour movement behaviors on children's psychosocial health when transitioning from primary to secondary school. This study described changes in 24-hour domain-specific movement behavior composition and explored their associations with changes in psychosocial health during this transition. Data were drawn from the Longitudinal Study of Australian Children. The analytical sample (n = 909) included children who were enrolled in primary school at baseline (2010) and in secondary school at follow-up (2012). Time spent in 8 domains of movement behaviors was derived from the child-completed time-use diaries. Psychosocial health was examined using the self-report version of the Strengths and Difficulties Questionnaires. Analyses included repeated-measures multivariate analysis of variance and compositional regression. Children reported engaging in more social activities and sleeping less over the transition period. Increased time spent in social activities (βilr = -0.06, P = .014) and recreational screen use (βilr = -0.17, P = .003) (relative to other domains) were associated with decreased prosocial behavior in boys. Changes in movement behavior composition were not associated with changes in girls' psychosocial health. This study found considerable changes in children's 24-hour movement behavior composition, but a lack of consistent association with changes in psychosocial health during the primary to secondary school transition.
Journal of Physical Activity and Health
Keywords: Adolescents and youth; Health and wellbeing